Two new genera of long clawed Isohypsibioidea Guil, Jørgensen & Kristensen, 2019 - Kaczmarek, Łukasz; Bartylak, Tomasz; Roszkowska, Milena (Zootaxa, 2020)
Two new eutardigrade genera Vladimirobius gen. nov. and Weglarskobius gen. nov. are erected for the species Grevenius irregibilis (Biserov, 1992) and Isohypsibius altai Kaczmarek & Michalczyk, 2006a, respectively. They are characterized by strongly modified claws, bucco-pharyngeal apparatus of the Isohypsibius variant, pharyngeal apophyses, and placoids present. The primary branches of internal claws of Vladimirobius gen. nov. are wide in lateral view and have very prominent gibbosity-like projections, whereas primary branches of external claws are thin and extremely long. In Weglarskobius gen. nov. claws IV are similar in shape and size, but the primary branches are extremely long, and thin. Moreover, claws on legs I–III vary greatly in size and shape in Weglarskobius gen. nov. Such supposed autapomorphies fully justify erection of the two new genera, even if the genetic data are presently unavailable.